geofd: An R Package for Function-Valued Geostatistical Prediction - Ramón Giraldo (Revista Colombiana de Estadística, 2012)
Spatially correlated curves are present in a wide range of applied disciplines. In this paper we describe the R package geofd which implements ordinary kriging prediction for this type of data. Initially the curves are pre-processed by tting a Fourier or B-splines basis functions. After that the spatial dependence among curves is estimated by means of the tracevariogram function. Finally the parameters for performing prediction by ordinary kriging at unsampled locations are by estimated solving a linear system based estimated trace-variogram. We illustrate the software analyzing real and simulated data.